(untitled) (Journal of Libya for geographical studies, 2021)
The spatial distribution of ancient olive presses and their spread since antiquity has been linked to the spread of the olive tree in Bani Walid valley . The olive tree is one of the oldest agricultural facts found in Bani Walid valley , where its presence was linked to the fortified Roman farms that spread in the Bani Walid Valley and its tributaries, which date back to the first half of the third century AD. Its cultivation spread during the reign of Emperor Tiberius and expanded during the reign of Emperor Hadrian. This tree is still inhabiting Bani Walid valley until now, and what confirms this connection is the ruins of olive presses that were built by the people in the residential neighborhoods, and its ruins still mimic time. This study will discuss the ancient olive age mills in Bani Walid valley in three main axes: their basic components, the primitive age method, and the spatial distribution of the mills. The research ends with a set of results and recommendations.